The Validity of Song Modifications Made by Unknown Identities (Anonymous) Under the Copyright Law - Ahmad Khusnan Junaidi; Dwi Fidhayanti (Faculty of Law, Maranatha Christian University, 2025)
The rapid development of digital technology makes it easier for someone to disseminate music content illegally which causes harm to the creators or music copyright holders as a whole. This study aims to explain and analyze the validity of exclusive rights obtained by anonymous works that modify or rearrange other people's works. The research method used is normative juridical with a Legislative Approach and Conceptual Approach. Primary and secondary legal materials collected through literature study are then analyzed descriptively. The research findings show that the exclusive rights obtained by Anonymous for modifying other people's works without permission is an act of copyright infringement. So that the work produced by anonymous is considered invalid and cannot arise copyright, nor is it allowed for other parties to make new creations without the permission of the creator and / or copyright holder. Meanwhile, YouTube and TikTok have Terms of Service that regulate content uploads. However, there is a User Generated Content clause in TikTok which states that all uploaded content is not the responsibility of the platform. This research can contribute to the development of copyright law theory, especially related to the validity of exclusive rights to copyrighted works produced by anonymous identities.